1996
DOI: 10.1021/jm950626d
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 1,5-Benzodiazepines with Peripheral Cholecystokinin (CCK-A) Receptor Agonist Activity. 1. Optimization of the Agonist “Trigger”

Abstract: Directed screening of compounds selected from the Glaxo registry file for contractile activity on the isolated guinea pig gallbladder (GPGB) identified a series of 1,5-benzodiazepines with peripheral cholecystokinin (CCK) receptor agonist activity. Agonist efficacy within this series was modulated by variation of substituents on the N1-anilinoacetamide moiety. Remarkably, a single methyl group confers agonist activity, with an N-isopropyl substituent providing optimal efficacy. Hydrophilic substituents on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
87
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 27 publications
0
87
0
Order By: Relevance
“…A key molecule used in these studies was the 1,5-benzodiazepine developed at GlaxoSmithKline Research Laboratories, GI181771X, which has a unique functional profile, being a type 1 CCK receptor agonist and a type 2 CCK receptor antagonist (4,5). This provided an ideal ligand to study binding and activation mechanisms of the two closely related CCK receptors.…”
mentioning
confidence: 99%
“…A key molecule used in these studies was the 1,5-benzodiazepine developed at GlaxoSmithKline Research Laboratories, GI181771X, which has a unique functional profile, being a type 1 CCK receptor agonist and a type 2 CCK receptor antagonist (4,5). This provided an ideal ligand to study binding and activation mechanisms of the two closely related CCK receptors.…”
mentioning
confidence: 99%
“…In recent years, smallmolecule agonists have been described, even for receptors for larger hormones like insulin, TPO, and EPO (18)(19)(20), but none of these receptors belong to the GPCR superfamily. Within the GPCRs, small-molecule agonists have been described, e.g., for the arginine vasopressin V-2 receptor, the somatostatin receptor, the bradykinin receptor, the cholecystokinin receptor, the angiotensin II receptor, and the growth hormone secretagogue receptor (21)(22)(23)(24)(25)(26). However, none of these GPCRs belong to the B family, and the natural ligands are all either fairly small or have a defined secondary structure.…”
mentioning
confidence: 99%
“…43 It also provided molecular insights into the determinants of biological activity, with evidence for a key interaction between a 'trigger functionality' within a benzodiazepine agonist and the receptor residues it likely interacts with. 20 Once again, this model had great predictive power, being able to effectively distinguish CCK1R agonists from CCK1R antagonists. 43 This has provided clear evidence of the differences in the shape of this pocket when in inactive and active conformations.…”
Section: Characterization Of the Small-molecule Ligand-binding Pocketmentioning
confidence: 92%
“…10,15,16 Indeed, multiple companies were successful in developing small-molecule CCK agonists, with some of these agents entering into clinical trials. [17][18][19][20] Whereas those candidates that had been shown to be quite active in vitro in cell studies and in vivo in animal studies were also shown to reduce food intake in human clinical trials, these drugs were no better than acute dieting, the requirement that the Food and Drug Administration had in place for the approval of a diet drug. None of these agents advanced to being approved for clinical use.…”
Section: Cholecystokinin Physiologymentioning
confidence: 99%